A Rare Case of Giant Cystic Adenomatoid Tumor of the Uterus With Literature Review - Pranav S. Renavikar; Lina Adwer; David G. Wagner; Subodh M. Lele (Hindawi Limited, 2024)
Adenomatoid tumors are rare benign neoplasms arising from mesothelial cells, commonly found in the female genital system, particularly the uterus and fallopian tubes. The giant cystic variant of adenomatoid tumor is exceptionally rare and can cause massive growth mimicking malignant gynecological conditions. Histology and immunohistochemistry play a crucial role in confirming the diagnosis, with markers such as calretinin, D2-40, CK7, BAP1, ER, and WT1 proving useful. A 51-year-old female with a history of breast cancer presented with pelvic pressure and vague pain. Imaging revealed an enlarged uterus with multiple heterogeneously enhancing masses and a predominantly cystic mass arising from the fundus, all believed to be leiomyomas. Surgical exploration and subsequent pathologic examination identified the cystic tumor as cystic adenomatoid tumor coexisting with leiomyomas, adenomyosis, and abdominal endometriosis. Diagnosing cystic adenomatoid tumor presents challenges, especially in patients with complex gynecologic histories. Cystic adenomatoid tumors typically have a favorable prognosis following surgical intervention. This case demonstrates one of the few reports of a giant cystic adenomatoid tumor (11.5 cm) and highlights diagnostic mimics. As these tumors are typically small and often seen only microscopically, the large size can confuse the pathologist who may be unaware of this feature leading to a misdiagnosis.